2002
DOI: 10.1128/aem.68.6.2644-2650.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of OpuC as a Chill-Activated and Osmotically Activated Carnitine Transporter in Listeria monocytogenes

Abstract: The food-borne pathogen Listeria monocytogenes is notable for its ability to grow under osmotic stress and at low temperatures. It is known to accumulate the compatible solutes glycine betaine and carnitine from the medium in response to osmotic or chill stress, and this accumulation confers tolerance to these stresses. Two permeases that transport glycine betaine have been identified, both of which are activated by hyperosmotic stress and one of which is activated by low temperature. An osmotically activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 28 publications
4
43
0
2
Order By: Relevance
“…Indeed, in the only previous study on L. pneumophila physiology at low temperature, Mauchline et al found increases in the amount of unsaturated fatty acids in bacteria grown at 24°C (52). Newly recognized forms of cold adaptation are increases in trehalose and palmitoylated lipid A within E. coli (41,87) and solute (e.g., glycine, betaine) uptake in Listeria monocytogenes (3,49). The ability of wild-type L. pneumophila to stimulate, in trans, low-temperature growth of lsp mutants suggests that low-temperature-in- VOL.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the only previous study on L. pneumophila physiology at low temperature, Mauchline et al found increases in the amount of unsaturated fatty acids in bacteria grown at 24°C (52). Newly recognized forms of cold adaptation are increases in trehalose and palmitoylated lipid A within E. coli (41,87) and solute (e.g., glycine, betaine) uptake in Listeria monocytogenes (3,49). The ability of wild-type L. pneumophila to stimulate, in trans, low-temperature growth of lsp mutants suggests that low-temperature-in- VOL.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both the L. monocytogenes and the B. subtilis B regulons include multiple genes that have been shown experimentally to contribute to protection against osmotic stress, including genes encoding several solute transporters. The ABC transporter OpuC contributes to osmotic stress resistance by facilitating uptake of the osmoprotectants choline and glycine betaine in both L. monocytogenes and B. subtilis (1,35,36,60), and expression of the encoding operon is B dependent in L. monocytogenes. Similarly, lmo1421 and the B. subtilis homologue opuB, each of which is a member of the B regulon in its species, both encode a putative choline transporter which may also contribute to osmotic stress resistance (22,36).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation and response to chill stress have been studied in detail in Bacillus subtilis (9,15,45,46) and in Listeria monocytogenes (3,22,39). In B. subtilis, global responses at the level of the transcriptome and its contribution to low-temperature adaptation (7, 9) have been described, as well as the response at the level of fatty acid synthesis (21,46).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological responses and adaptation phenomena to chill stress have been reported for a number of prokaryotes, e.g., Bacillus subtilis, Listeria monocytogenes, and cyanobacteria (3,9,12,18,19,22,25,39,46); related systems have also been studied in plants and in humans (17,44).…”
mentioning
confidence: 99%